Promotion of Rice Variety NDR 8002 in Rainfed Lowland Condition of Eastern Uttar Pradesh - Verma, Saurabh; Singh, D. P.; Singh, N. K.; Singh, V. K. (International Journal of Bio-resource and Stress Management, 2023)
Rice is a main crop in the lowland condition of eastern Uttar Pradesh where it grows extensively under rainfed condition during monsoon months. The participatory approaches revealed the problem associated with rice cultivation and it has been found that there is need of a short to medium duration high yielding rice variety in lieu of the traditional medium long duration varieties to catch the rabi season in time. Considering the factual need of the farming community, the on farm trials and front line demonstrations has been planned by the KVK and conducted in an area of 30.0 ha involving 100 farmers in five adopted villages in five different blocks of Mau district. The results show that the yield of newly introduced rice variety NDR 8002 increased successively over the years in demonstration plots and with little increase in cost of cultivation under demonstration a higher return was achieved. Improved technology increased yield (35.08 q ha-1) over farmers’ practices by the margins of 49.02% in rice crop under rainfed conditions. Net profit of ` 17,905 ha-1 and B:C ratio of 1.95 was found with demonstrations and was much higher when compared with farmers’ practices (` 8,900 ha-1 and 1.56, respectively) in the crop under studied. The extension gaps for improved technologies were more than technology gaps and also the technology index was low, highlighted the need to educate the farmers in rapid adoption of improved technologies in rice crops.